Perancangan Aplikasi Android Bank Sampah Menggunakan Metode Object Oriented di Wilayah Salatiga - Christian Cahyaningtyas; Eko Sediyono (Institut Shanti Bhuana, 2023)
A trash bank is a place where used or recycled waste is collected by collectors who will later be used as craft materials or materials that can be useful and of high value. Currently, collectors and customers, in terms of buying and selling recycled waste, can only walk around the complex hoping that someone sells used goods and customers can only wait for collectors to pass by their homes. From these problems, this research was conducted to design a trash bank application using an object oriented method. And to design applications using the unified modeling language (UML). From this research results in designing an android application that in the future can be developed or implemented to the public. This application will be very useful and help collectors and customers.